Evolving global trends in PCOS burden: a three-decade analysis (1990–2021) with projections to 2036 among adolescents and young adults - Wang, Jiameng; Wang, Boyu; Li, Chengjia; Meng, Tianwei; Liu, Changxing; Chen, Jia; Guo, Ying (Frontiers in Endocrinology, 2025)
BackgroundPolycystic Ovary Syndrome (PCOS) is a common endocrine disorder affecting adolescent and young adult females, yet global data on its burden and trends remains limited.MethodsWe analyzed data from the Global Burden of Disease Study 2021 for females aged 10–24 years in 204 countries (1990-2021). Metrics included cases, age-standardized incidence (ASIR), prevalence (ASPR), disability-adjusted life years (ASDR), and average annual percentage changes (AAPCs). Future trends (2022-2036) and disease reduction gaps were assessed.ResultsFrom 1990 to 2021, global PCOS cases increased by 56% (incidence), 59% (prevalence), and 58% (DALYs). ASIR rose from 49.45 to 63.26 per 100,000, with an AAPC of 0.8. Southeast Asia, East Asia, and Oceania had the fastest growth, while high-SDI regions bore the highest burden. Girls aged 10–14 showed the steepest age-specific increase. Nationally, the largest increases occurred in Equatorial Guinea, Maldives, and Myanmar, while Italy saw a decline. Forecasts through 2036 indicate continued increases in ASIR (+8.32%), ASPR (+10.87%), and ASDR (+10.39%). Frontier analysis highlighted unachieved reduction potential, especially in high-SDI countries.ConclusionsPCOS burden among adolescents and young adults has significantly risen globally with disparities by region, SDI, and age, warranting urgent and equitable public health strategies.